A cobalt‐based metal – organic framework as cocatalyst on BiVO4 photoanode for enhanced photoelectrochemical water oxidation - Zhang, Wang (2020)
A metal–organic framework (MOF)‐modified bismuth vanadate (BiVO4) photoanode is fabricated by an ultrathin sheet‐induced growth strategy, where ultrathin cobalt oxide sheets act as a metal source for the in situ synthesis of Co‐based MOF poly[Co2(benzimidazole)4] (denoted [Co2(bim)4]) nanoparticles on the surface of BiVO4. [Co2(bim)4] with small particle size and high dispersion can serve as a promising cocatalyst to accept holes transferred from BiVO4 and boost surface reaction kinetics for photoelectrochemical (PEC) water oxidation. The photocurrent density of a [Co2(bim)4]‐modified BiVO4 photoanode can achieve 3.1 mA cm−2 under AM 1.5G illumination at 1.23 V versus the reversible hydrogen electrode (RHE), which is better than those of pristine and cobalt‐based inorganic materials‐modified BiVO4 photoanodes. [Co2(bim)4], with porosity and abundant metal sites, exhibits a high surface charge‐separation efficiency (83 % at 1.2 V versus RHE), leading to the enhanced PEC activity. This work will bring new insight into the development of MOF materials as competent cocatalysts for PEC water splitting applications.